Does the Genitive Operate in the Hungarian Case System?: I. The é-Genitive - Bielecki, Robert (Lingua Posnaniensis, 2011)
After three centuries of discussion concerning the genitive case in Hungarian, the authors of the latest academic grammars - in contrast to many of their predecessors - no longer distinguish this casal category. Different cases in Hungarian should, according to them, be distinguished only on the basis of their forms (endings). Such an extreme unilateral approach to this category seems to have simplified at first sight the description of the Hungarian language, erasing from it any case syncretism. From the point of the view defended in the present paper, however, talking about linguistic entities without taking into account their meaning is illusory; even in the case of meaningless speech segments such as phonemes it is the meaning of the segments in which they occur that constitutes the ultimate instance allowing them to be distinguished at all. The same applies to case. The moderate approach to the category of case adopted here, taking simultaneously into account its (i) morphological, (ii) semantic and (iii) syntactic properties, leads irrevocably to the restoration of the genitive in the description of the Hungarian language. As a specific feature of this language one should consider the sharp distinction between two subclasses of the genitive case: (i) the non-attributive (é-genitive) and (ii) the attributive genitive (Ø-/nak-/nek-genitive). Only the first of these (the é-genitive) will be discussed in detail. The second (the Ø-/nak-/nek-genitive) will be the subject of a continuation of the present paper. Recognition of the é-genitive seems to have been blocked by those of its properties which seem to be quite incongruous with those of other Hungarian cases. It is claimed, for example, that the marker -é - unlike the markers of other cases - seems not to express any syntagmatic function. This function is expressed by the case marker attached after the morpheme -é (A diákét (láttam) '(I saw) The student's one'). In the view of the author, however, the lack of syntagmatic function in the case of the morpheme -é is not so obvious. On the other hand, such "discrediting" properties for a case marker candidate, as the property of not occupying the final morphotactical position (diákét), can be viewed as entirely irrelevant for the category of case. The adopted approach seems to make possible a description of this fragment of the Hungarian case system from a more homogenous perspective, showing the interplay of different casal meanings within the boundaries of one word.